Detection of Escherichia coli Contamination using Most Probable Number (MPN) methods in Chicken Meats in Market of Surabaya - Wardhana, Dhandy Koesoemo; Safitri, Devi Ayu; Annisa, Suwaibatul; Effendi, Mustofa Helmi; Harijani, Nenny (Jurnal Medik Veteriner, 2021)
Foodborne diseases are diseases transmitted through contaminated food and are one of the main public health problems. The bacteria that usually contaminates chicken meat is Escherichia coli. E. coli contamination in chicken meat can affect consumer health. Chicken meat processing and market conditions affect the level of bacteria contamination. This study aims to measure the contamination of E. coli bacteria in chicken meat in Surabaya's markets. The method which used to count and estimate the number of E. coli bacteria found in chicken meat in this study was Most Probable Number (MPN). The results showed 20 samples (33.3%) from 60 samples gave negative results. This indicated that only 20 samples of chicken meat were safe for consumption because the MPN value is <1 í— 101 CFU/g while the remaining 40 samples (66.7%) were not safe for consumption because the MPN value is> 1 í— 101 CFU/g. The standard of SNI 3924: 2009 concerning the minimum requirement for the amount of E. coli contamination in chicken meat is 1í—101 CFU/g so that the contamination of E. coli which found in chicken meat in Surabaya was high.